Intercomparison of four algorithms for detecting tropical cyclones using ERA5 - S. Bourdin; S. Fromang; W. Dulac; J. Cattiaux; F. Chauvin (Geoscientific Model Development, 2022)
The assessment of tropical cyclone (TC) statistics requires the direct, objective, and automatic detection and tracking of TCs in reanalyses and model simulations. Research groups have independently developed numerous algorithms during recent decades in order to answer that need. Today, there is a large number of trackers that aim to detect the positions of TCs in gridded datasets. The questions we ask here are the following: does the choice of tracker impact the climatology obtained? And, if it does, how should we deal with this issue?